Remoção e vivências de prazer-sofrimento de servidores técnico-administrativos da Universidade Federal de São Carlos - Loureiro, Thiago (Universidade Federal de São Carlos, 2015)
The central theme of this study is the technical and administrative work in education of assistant position occupants in administration at the Federal University of São Carlos (UFSCar), São Carlos campus, who have experienced the removal process. We aimed to identify feelings of pleasure and suffering experienced by servers and verify the defensive strategies they used to cope with the feelings of suffering arising from the work environment. Under the theoretical aspect, the study references the dejourian’s Psychodynamics Work, a line of studies that has been used by different areas of knowledge in the characterization of the elements present in the experience of the workers. Suffering at work is a ubiquitous phenomenon of nature, and has been the subject of research in a variety of occupations. From this perspective, the public servant of Federal Institutions of Higher Education (IFES) covers this scenario. In terms of methodology, a study was conducted based on exploratory research, qualitative approach, using the case study method in a sample of eight subjects. The central categories of analysis were suffering, pleasure, labor relations, recognition and defense strategies of the servers facing labor contingencies. A thematic content analysis was made, based on various aspects of the daily work of the administrative assistant, such as the stigma of a public servant; seasonality of managers; patrimonialist behaviors; taking work thoughts home; political influence; bullying; somatization; the intensification of work; and the invisibility of middle activities. These were suffering indicators of servers. Among the pleasure indicators stood out working conditions; the symbolic fee; the public space for discussion; work in an educational institution. In this plot of pleasure and suffering, recognition appears as an essential element. It was possible to point to the ambivalence in labor relations and daily autonomy in the workplace. The main strategies to deal with adversity and suffering were prioritizing the study; verbalize problems; documenting complaints; coping; isolation; and indifference. We consider work as a central element in the ability of the worker to establish himself as a social being. The results allowed the understanding of different aspects of the work of TAE server, from the experiences of pleasure and suffering, passing by the intersubjective relations of the same. In the cutting we made, the removal was successful in most cases, helping this professional category in the redefinition of work, as well as the preservation of health. However, there were also cases where the removal accentuated possible suffering experiences. This study made expanding the universe of work psychodynamics knowledge possible in this professional category, revealing the processes in mental and social-relational scope involving the meanings of work for man.
Keywords: Trabalho; Sofrimento; Prazer; Remoção; Técnico-administrativo em educação; Labour; Technical and administrative education; Pleasure; Suffering; Removal; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ADMINISTRACAO DE PESSOAL; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA